Hierarchical porous carbon microtubes derived from willow catkins for supercapacitor applications. Issue 5 (14th December 2015) - Xie, Lijing; Sun, Guohua; Su, Fangyuan; Guo, Xiaoqian; Kong, Qingqiang; Li, Xiaoming; Huang, Xianhong; Wan, Liu; song, Wen; Li, Kaixi; Lv, Chunxiang; Chen, Cheng-Meng
Abstract : Hierarchical porous carbon microtubes derived from willow catkins exhibited excellent electrochemical performances in both aqueous and organic electrolytes. Abstract : With willow catkins as highly accessible carbon sources, hierarchical porous carbon microtubes (denoted as HPNCTs) have been successfully prepared by a facile carbonization and subsequent KOH activation process. The resulting materials not only inherited the natural tubular morphology of willow catkins, but also developed a hierarchical porous structure by activation, with nitrogen from the biomass being self-doped in the resulting carbon. A maximum specific surface area of 1775.7 m 2 g −1 with a pore volume of 0.8516 cm 3 g −1 was achieved for HPNCT-800. When evaluated as an electrode by a three-electrode system in 6 M KOH aqueous solution, the material exhibited a high gravimetric capacitance of 292 F g −1 at a current density of 1 A g −1, with a good rate capability of 83.5% retention at 10 A g −1 . HPNCT-800 was further employed in a coin-type symmetric device with 1 M LiPF6 electrolyte, and exhibited a high energy density of 37.9 W h kg −1 at a power density of 700 W kg −1, with excellent cycling stability with 90.6% retention after 4000 cycles. By taking advantage of the unique structure of abundant biomass from nature, this work sheds light on the creation of advanced porous carbon materials towards energy storage applications.